Effect of muscle fatigue on posture control in soccer players during the short-pass movement - Manfredini Baroni, B.; Joner Wiest, M.; Abeche Generosi, R.; Vaz, M. A.; Pinto Leal Junior, E. C. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
Muscle fatigue is characterized by the inability to generate or maintain an expected effort or force level and negatively affects sports performance. One of the functional consequences of fatigue is a decrease in static and dynamic postural stability. The objective of this study was to evaluate the effect of muscle fatigue induced by high-intensity exercise on the dynamic postural stability of soccer players during the characteristic motor action of the sport: the short-pass. Twenty-seven male soccer players aged 14 to 16 years performed the short-pass movement on a stabilometric platform before and after a high-intensity exercise protocol performed on a cycle ergometer. After the fatigue protocol, the athletes presented a 31% increase in the mean velocity of the center of pressure displacement. Moreover, although the difference in the center of pressure displacement amplitude in the medial-lateral direction (15%) was not significant, displacement increased by 22% in the anterior-posterior direction. It was concluded that muscle fatigue promotes a decrease of postural stability during the short-pass movement in soccer players, probably compromising the sports performance of the athletes.